Biological, psychological, and social factors in complicated grief - Wulandari , Ratna; Kusumawati, Mira Wahyu; Albyn, Devanda Faiqh (Promotion and Prevention in Mental Health Journal, 2021)
Individuals fail to follow the normative grieving process within a long time and stay in one phase, so it manifests in physiological function and disrupts their life function. This article aims to analyze the role of aspects affecting the problem of complicated grief. A literature review method used is doing a scientific article review obtained from the database. Articles were obtained by browsing online databases, such as Science Direct, EBSCO, and Proquest, with keywords "grief" or "grieving complicated". The inclusion criteria is the research article about predisposition factors causing complicated grief, reviewed by three aspects, namely biological, psychological and social. The exclusion criteria are the systematic review or meta-analysis article. Articles limited to the last ten years, from 2011 to 2020, ensure that the article is relevant to the current condition.  The result from this review are biological factors (genetic, neurotransmitter, health status, substance usage history, and history of having family member with mental disorder), psychological factors (personality type, family relationships, intelligence level, past experience, self-concept, and psychological defense), social factors (age, gender, education level, economic status, social status, cultural background, religion and beliefs, and place of environment). Predisposition factors of complicated grieving can be reviewed from three factors, namely biological, psychological and social. A right coping source is needed so that a person can go through grieving time.